Advances in multifunctional balanced ventilation technology for dwellings and arising challenge to quantify energy efficiency and renewable generation contributions using international test standards. (December 2020) - Hunt, David; Mac Suibhne, Naoise; Dimache, Laurentiu; McHugh, David; Lohan, John
Abstract: This paper evaluates the ability of EN16573:2017 to isolate and quantify the energy efficiency and renewable generation contributions of multifunctional balanced ventilation systems. These systems integrate an air-source heat pump with heat recovery ventilation and two similar, yet physically different configurations (C1 and C2) are assessed. Heat pump operation does not influence heat recovery performance for widely used configuration C1 but does influence for novel configuration C2. This study shows that while EN16573:2017 can isolate the energy efficiency (heat recovery exchanger) and renewable generation (heat pump) contributions for configuration C1, it fails when applied to configuration C2. Measurements undertaken using EN16573:2017 on configuration C2 revealed an overall coefficient of performance of 5.07, split 51% heat exchanger with heat pump off (phase 1), and 49% heat pump (phase 2 minus phase 1). If this result were obtained for configuration C1 the respective contributions would be 51% energy efficiency and 49% renewable generation. While these contributions cannot be resolved using EN16573:2017 for configuration C2, it can be achieved using two additional measurement planes in the incoming airstream. These showed an 88%:12% contribution from the heat exchanger and heat pump, respectively. While accurate, this result under-estimates the true heat pump contribution, as its positive impact on the heat exchanger efficiency boosts its contribution from 51% (phase 1) to 88% (phase 2). This paper acknowledges that heat pump operation leverages a 37% increase in heat exchanger performance and proposes a that the respective contributions of the heat exchanger and heat pump should be 42%:58%. Highlights: Novel combined heat recovery ventilation system is experimentally investigated. Additional measurement planes are required beyond the EN 16573-2017 standard. Energy efficiency and renewable generation are individually assessed in a dynamic system.